A propriedade em jogo com a liberdade: uma história da última década da escravidão em Pindamonhangaba/SP - Castilho, Mateus Henrique Obristi (2022)
The present thesis aims at understanding the historical process which culminated with the grants of letters of freedom (with or without conditions), on the eve of the abolition, between February 16th and 26th, processed, in this way, in ten days, by the owners, members of the slaveholding stratum, to their enslaved, occasioning, therefore, in the municipality of Pindamonhangaba, the supposed passage from slavery to freedom for women, children, and men. The paper is structured into two parts. The first deals with the landlord's perspective and the legality of the emancipation process. The interpretation of the process that culminated with the abolition of slavery in Pindamonhangaba is known by reading and analyzing the Tribuna do Norte newspaper, a liberal newspaper of the local press, founded on June 11th, 1882, published weekly, always on Sundays, through the efforts of the local liberal political faction. In this research, the editorials that, in some way, dialogued with the Brazilian slavery issue and the problem of slave emancipation are privileged to be analyzed. The main articulator of the newspaper's position was its only editor, João Marcondes de Moura Romeiro. While the second part focuses on the analysis of the understanding of the desires and struggles for freedom of the enslaved subjects in Pindamonhangaba/SP, from the reading, as historical sources, of the civil lawsuits for freedom, which enables a more expressive portrait of this process and its protagonists. For this research, the sources used are the emancipation fund freedoms and freedom actions. They are, therefore, documents containing lawsuits filed by slaves in court against their masters, requesting their freedom, even in default, which became a constant in the 1880s in the locality. Privileging, thus, the slave actions for the end of slavery through the legal arena in which the judiciary became a singular stage of the right to be free